Wakaf Produktif Berbasis Digital Sebagai Instrumen Pengembangan Kebijakan Moneter Islam - Diniyah Sukma, Eny Lathifah (Al-Musthofa: Journal of Sharia Economics, 2020)
The purpose of this study is to determine the role of digital-based productive waqf in the Islamic financial institution as an instrument for developing Islamic monetary policy. This research uses library research method. The research data were collected through text reading and then analyzed using descriptive analytical methods. The result of this research is that the Islamic monetary policy in Indonesia can be developed through digital-based productive waqf instruments developed by Islamic financial institution in the form of programs managed by waqf management institutions in Indonesia, so that prosperity is achieved in life and is able to increase the development of the Islamic economy.